Radon From the Ground into Our Schools: Parent and Guardian Awareness of Radon. (March 2020) - Martin, Kirsten; Ryan, Rebecca; Delaney, Thomas; Kaminsky, David A.; Neary, Scott J.; Witt, Ethan E.; Lambert-Fliszar, Florence; Remy, Kyle; Sanford, Shawn; Grenoble, Kathryn; Carney, Jan K.
Radon is the leading cause of lung cancer among non-smokers. Exposure in schools may be harmful to schoolchildren and staff. However, states differ considerably in their approaches to mandating radon testing and mitigaiton in schools. In this study, 126 survey responses were received and analyzed from parents of K-12 children in Vermont, USA. Qualitative data were obtained by interviewing two parents for their views and concerns about radon in schools. Our results showed that only 51% of parents believed that radon affects the lungs and only 39% identified it as a carcinogen. 91% believed their children's schools should act to address elevated radon levels and 87% supported mandated mitigation. These data suggest that there is already overwhelming support for radon regulation in schools among parents of K-12 children. Parents with children in elementary school were significantly more likely to support radon testing, mitigation, and legislation than parents with older children. This suggests that these parents may be strong advocates to encourage legislative action. Parents with more knowledge about radon were significantly more likely to support radon testing in schools. Educating parents about exposure to radon at school and its association with lung cancer could strengthen existing community support for legislation mandating radon testing and mitigation.